Comparative Analysis of Technical Efficiency of Milk Production Systems in Uasin Gishu County of Kenya - Kibiego, Michael B; Lagat, Job K; Bebe, Bockline O (International Journal of Business, Economics and Management, 2015)
In Uasin Gishu County the rapidly declining household land sizes are a pre-requisite to increased intensification in dairy production. Although the three dairy production pathways are used by farmers in the County, it has not been established which one of them would be comparatively competitive to enhance commercialization process and lead to attractive returns to smallholders investing in milk production. The objective of this paper was to determine the economic efficiency of smallholder milk production under different intensification methods. A sample size of 246 smallholder dairy farmers was selected in Uasin Gishu County using stratified random sampling method. Using both primary and secondary data, economic efficiencies were evaluated utilizing Cobb-Douglas stochastic frontier production function. The result of the analysis indicate that presence of technical inefficiencies had effects in milk production as depicted by the significant estimated gamma coefficient of each model, the generalized likelihood ratio test and the predicted economic efficiencies within the dairy farms. Technical efficiency increased with the level of intensification of milk production with open grazing, semi-zero grazing and zero grazing recording a mean score of 0.54, 0.57 and 0.81 respectively. The maximum likelihood estimates for technical efficiency was an increasing function of cost of feeds and equipment in the three production systems with statistical significance of 5%. Market access condition the technical efficiency of milk production especially for this highly perishable product. Educational opportunities for farmers lead to initiative, innovation and improvements. There is need to increase the level of intensification in milk production to enhance technical efficiency.